(untitled) (Mustansiria Dental Journal, 2024)
The relationship between changes in postmenopausal women and periodontal condition had been studied in many countries. It has been suggested that estrogen deficiency may play a role in periodontal disease following menopause. The aim of this study was to investigate the influence of postmenopausal alteration on the clinical periodontal parameters and teeth loss. In addition, to determine the relationship between systemic bone mineral density and periodontal disease in postmenopausal .women Sixty Iraqi women in total were involved in this study, 20 women as a control group of age (35-45) years and forty postmenopausal women divided into two .subgroups: groupl for age (50-60) years and group 2 of age (60-70) years :Questionnaire involved the following periodontal parameters Plaque index (PI), gingival index (GI), bleeding on probing (BOP), pocket depth (PD), clinical attachment level (CAL). All these parameters were measured and tabulated according to redefined scores, or counts, and the data was analyzed .statistically - Fifteen of forty postmenopausal women, were examined using dual energy x ray absorptiometry (DEXA) equipment to measure bone mineral density (BMD) in order to determine the relationship between (BMD) and any of the above periodontal parameters. The means, Gl, BOP, PD and CAL were found to be significantly higher .)in the postmenopausal group than the control (P<0.05 It was found that BMD is negatively associated with Gl, BOP, PD and CAL but the correlation is either of high significant or of slight of difference but not significant at (P<0.05). The clinical parameters may increase depending on the expected negative effects during menopause further, it is concluded that BMD of the .lumbar spine is related to CAL, PD, number of teeth loss and to a lesser extent BOP